Towards global SEEA Air Emission Accounts Description and evaluation of the OECD methodology to estimate SEEA Air Emission Accounts for CO2, CH4 and N2O in Annex-I countries to the UNFCCC - Flachenecker, Florian (OECD Statistics Working Papers, 2018)
This paper describes and evaluates the OECD methodology to estimate Air Emission Accounts (AEAs) for carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O), in line with the System of Environmental Economic Accounting (SEEA)